Heritage Coeducation in prehistoric archaeology: a tool to apply the gender perspective to the spread of Prehistory - Cacheda Pérez, Maria (Clio. History and History Teaching, 2021)
This article presents a diagnostic tool in heritage coeducation for the dissemination of Prehistoric Archaeology, which can be implemented in museums and heritage institutions that work on the dissemination of Prehistory. This tool, in the form of an evaluation rubric, is built from a new methodology, the Heritage Coeducation (Cacheda Pérez, 2019, 2020), which consists of applying the gender perspective to the heritage educational action through the story that is explained, the educational action itself (relational sphere), and the language.The idea is to propose alternatives for action in heritage education for the dissemination of prehistoric heritage, which will have an impact on an equitable, fair and free education that will allow both boys and girls to develop the tools to live in society in a more democratic way.
Keywords: Coeducation, patrimonial education, heritage, feminism, archaeology, prehistory, social justice